Mineral chemistry of a Cenozoic igneous complex, the Urumieh-Dokhtar magmatic belt, Iran: Petrological implications for the plutonic rocks - Honarmand, Maryam; Omran, Nematollah Rashidnejad; Neubauer, Franz; Nabatian, Ghasem; Emami, Mohammad Hashem; Bernroider, Manfred; Ahmadian, Jamshid; Ebrahimi, Mohammad; Liu, Xiaoming (The island arc, 2016)
The Niyasar plutonic complex, one of the Cenozoic magmatic assemblages in the Urumieh‐Dokhtar magmatic belt, was the subject of detailed petrographic and mineralogical investigations. The Niyasar magmatic complex is composed of Eocene to Oligocene mafic rocks and Miocene granitoids. Eleven samples, representing the major rock units in the Niyasar magmatic complex and contact aureole were chosen for mineral chemical studies and for estimation of the pressure, temperature, and oxygen fugacity conditions of mineral crystallization during emplacement of various magmatic bodies. The analyzed samples are composed of varying proportions of quartz, plagioclase, K‐feldspar, hornblende, biotite, titanite, magnetite, apatite, zircon, garnet, and clinopyroxene. Application of the Al‐in‐hornblende barometer indicates pressures of around 0.2 to 0.4 kbar for the Eocene–Oligocene mafic bodies and around 0.5 to 1.7 kbar for the Miocene granitoids. Hornblende‐plagioclase thermometry yields relatively low temperatures (661–780 °C), which probably reflect late stage re‐equilibration of these minerals. The assemblage titanite–magnetite–quartz as well as hornblende composition were used to constrain the oxygen fugacity and H2O content during the crystallization of the parent magmas in the Miocene plutons. The results show that the Miocene granitoids crystallized from magmas with relatively high oxygen fugacity and high H2O content (~5 wt% H2O). The Miocene granitoids show similar range of oxygen fugacity, H2O contents and mineral chemical compositions, which indicate a common source for their magmas. Although the crystallization pressures of the Miocene plutons discriminate various categories of plutonic bodies emplaced at depths of about 5.7–6.5 km (Marfioun pluton), about 4.2 km (Ghalhar pluton) and 1.9–2.3 km (Poudalg pluton), they were later uplifted to the same level by vertical displacement of faults. The emplacement depths of the Niyasar plutons suggest that the central part of the Urumieh‐Dokhtar magmatic belt has experienced an uplift rate of ca. 0.25–0.4 mm/yr from the Miocene onwards. Urumieh‐Dokhtar火成岩帯の新生代火成岩類の一つであるNiyasar深成複合岩体について詳細な記載岩石学・鉱物学的研究を行った.Niyasar火成複合岩体は始新世から漸新世のマフィック岩と中新世の花崗岩類からなる.Niyasar火成複合岩体とその接触変成帯から採取した11試料について鉱物組成を分析し,各岩体の定置時の晶出温度・圧力,酸素分圧を推定した.分析試料は石英,斜長石,カリ長石,普通角閃石,黒雲母,チタナイト,磁鉄鉱,燐灰石,ジルコン,ザクロ石,単斜輝石からなる.普通角閃石Al圧力計は始新世―漸新世マフィック岩体について0.2―0.4 kbar,中新世花崗岩類について0.5―1.7 kbarを示す.普通角閃石―斜長石温度計は比較的低温(661–780 ˚C)を示すが,これは後の再平衡によるものと思われる.中新世深成岩類のチタナイト―磁鉄鉱―石英組合せと普通角閃石組成からマグマが固化した時の酸素分圧と含水量を制約した.その結果,中新世花崗岩類は比較的高い酸素分圧と高含水量(およそ5 wt%)のマグマから晶出したことがわかった.中新世花崗岩類は同様の酸素分圧,含水量,鉱物組成を示すことから,同じ起源物質に由来すると考えられる.中新世深成岩類の晶出圧力は様々な定置深度5.7―6.5 km(Marfioun深成岩体), ~4.2 km(Ghalhar深成岩体),1.9–2.3 km(Poudalg深成岩体)を示すが,後の断層運動によって同じ深さにまで上昇した.Nayasar深成岩体の定置深度はUrumieh‐Dokhtar火成岩帯中央部が中新世以降年間0.25―0.4 mmの速度で上昇したことを示唆する. The mineral chemistry of the Niyasar plutonic complex were used to investigate the physicochemical parameters during crystallization of magma.